An Analysis of Students Problem To Pronounce Aspirated /P/, /T/, /K/ at Initial Position of English Words - Widya Juli Astria (Fakultas Sastra Universitas Ekasakti, 2020)
The purpose of this research was to analyze the third semester students’ problem in learning English basic sounds pronunciation. The research design was case study. The data were collected by recording the students’ pronunciation. The subject of the research were the third Semester Students of English Department at Universitas Ekasakti). The result of the research was found that Each aspirated /p/, /t/, /k/ have two allophones, [ph] and [p], [th] and [t], [kh] and [k]. Then, all instances of [ph] occured immediately before a stressed vowel. It can be said that the following rule: /p/ becomes [ph] when it occured before a stressed vowel or initial position of English words. Moreover, aspirated /p/, /t/, /k/ sounds were really pronounced in two different ways. First, when these sounds came at the beginning of the word they are always followed by a puff of breath. Second, if aspirated /p/, /t/, and /k/ occur at the end of final position of English words, it is not necessary to pronounce them by following a puff of breath. In following there is a chart of aspirated /p/, /t/, /k/ sounds at initial position of English words